Prevalence and diversity of gastrointestinal helminths in free-ranging Asian house shrew (Suncus murinus) in Bangladesh - Rahman, Mizanur (Vet World, 2018)
BACKGROUND AND AIM: Asian house shrew (Suncus murinus), a widely distributed small mammal in the South Asian region, can carry helminths of zoonotic importance. The aim of the study was to know the prevalence and diversity of gastrointestinal (GI) helminths in free-ranging Asian house shrew (S. murinus) in Bangladesh. MATERIALS AND METHODS: A total of 86 Asian house shrews were captured from forest areas and other habitats of Bangladesh in 2015. Gross examination of the whole GI tract was performed for gross helminth detection, and coproscopy was done for identification of specific eggs or larvae. RESULTS: The overall prevalence of GI helminth was 77.9% (67/86), with six species including nematodes (3), cestodes (2), and trematodes (1). Of the detected helminths, the dominant parasitic group was from the genus Hymenolepis spp.(59%), followed by Strongyloides spp.(17%), Capillaria spp. (10%), Physaloptera spp. (3%), and Echinostoma spp.(3%). CONCLUSION: The finding shows that the presence of potential zoonotic parasites (Hymenolepis spp. and Capillaria spp.) in Asian house shrew is ubiquitous in all types of habitat (forest land, cropland and dwelling) in Bangladesh. Therefore, further investigation is crucial to examine their role in the transmission of human helminthiasis.